What is ZPD and what are the implications of ZPD for teaching? - Wang, Di (International Journal of Humanities and Education Development (IJHED), 2022)
Sociocultural theory was established by Vygotsky, and it analyzes the social and cultural attributes of the development mechanism of human psychological function based on the view of development and history (Xi, 2020). Vygotsky divided human psychological function into low-level psychological function as the result of biological evolution and high-level psychological function formed by the development of social culture and history. Focusing on the development of high-level psychological function of individuals, Vygotsky put forward three core concepts: internalization, mediation and zone of proximal development (ZPD). In this article, one of the core concepts, ZPD, will be discussed.